2019
DOI: 10.1002/ece3.4914
|View full text |Cite
|
Sign up to set email alerts
|

The contrasting hidden consequences of parasitism: Effects of a hematophagous nematode (Uncinaria sp.) in the development of a marine mammal swimming behavior

Abstract: Parasites are an important part of ecosystems, playing a critical role in their equilibrium. However, the consequences of parasitism beyond the direct effects associated with disease and mortality are not completely understood. This gap in knowledge is in part due to the difficulties to isolate the effect of single parasite species on physiological and behavioral traits in natural systems. The South American fur seal ( Arctocephalus australis )–hookworm ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…A significantly lower peripheral eosinophil cell count in ivermectin-treated Australian sea lion pups persisting to the second recapture 36–41 days post-treatment is consistent with previous reports in this and other otariid species ( Marcus et al, 2015b ; Michael et al, 2021a ; Montalva et al, 2019 ; Seguel et al, 2019 ), and indicates the elimination of parasite-associated eosinophilic tissue inflammation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A significantly lower peripheral eosinophil cell count in ivermectin-treated Australian sea lion pups persisting to the second recapture 36–41 days post-treatment is consistent with previous reports in this and other otariid species ( Marcus et al, 2015b ; Michael et al, 2021a ; Montalva et al, 2019 ; Seguel et al, 2019 ), and indicates the elimination of parasite-associated eosinophilic tissue inflammation.…”
Section: Discussionsupporting
confidence: 90%
“…The absence of a similar benefit to second recapture at 36–41 days post-treatment indicates that any growth rate benefit from hookworm elimination is short-term in the Australian sea lion, similar to the finding in the previous study at this site ( Marcus et al, 2015b ). In other otariid species ivermectin hookworm treatment has contributed to significant growth rate improvements measured over various time periods, including in northern fur seal pups (absolute growth rate over 2.5 months) ( DeLong et al, 2009 ), in New Zealand sea lion pups (absolute and relative growth rates over 10–93 days [mean 68 days]) ( Chilvers et al, 2009 ), and in South American fur seal (Arctocephalus australis) pups (absolute growth rate over >20 days versus a severely infected pup group) ( Montalva et al, 2019 ). Varying parasite impact on host (parasite species, hookworm infection intensity), differences in methodology for measurement of growth rate and time to resampling may explain these differences ( Chilvers et al, 2009 ; DeLong et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the spatial resolution of this data is ∼11 km, the values of the different squares within the potential foraging areas were averaged for a single day. This approach was used to represent all the potential foraging areas of fur seals at Guafo Island based on the previous studies on the duration of SAFS foraging trips ( Seguel et al 2018 ; Montalva et al 2019 ). Since the main SASL colony at Guafo Island is located ∼20 km south from the SAFS colony, these areas likely overlap with SASL foraging areas although data on the SASL foraging areas at Guafo Island are not available.…”
Section: Methodsmentioning
confidence: 99%
“…After treating some individuals with antihelminthic medication, they monitored behavior and weight gain in medicated and nonmedicated (still infected) pups. They found that growth rate was stunted in severely infected individuals, also coinciding with lower blood hemoglobin levels (Montalva, Perez‐Venegas, Gutierrez, & Sefuel, ). This resulted in behavioral differences.…”
Section: Beyond Mortality: Potential Significance Of Corynosoma Enhydmentioning
confidence: 99%
“…This resulted in behavioral differences. Severely infected pups spent more time in the water and spent that time swimming rather than playing (Montalva et al, ). It should be noted that Uncinaria spp.…”
Section: Beyond Mortality: Potential Significance Of Corynosoma Enhydmentioning
confidence: 99%